Inhibitory effect of curcumin on proliferation of K562 cells involves down-regulation of p210(bcr/abl) initiated Ras signal transduction pathway - Wu Li-Xian; Xu Jian-Hua; Wu Guo-Hua; Chen Yuan-Zhong (Acta Pharmacologica Sinica; Vol 24, No 11 (November 2003): Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effects of curcumin (Cur) on proliferation of K562 cells and the relationship between these effects and Ras signal transduction pathway activated by p210bcr/abl. METHODS: K562 cell line was used as a p210bcr/abl-positive cell system and HL-60 cell line as a p210bcr/abl-negative control; etoposide (VP-16), which has no influence on p210bcr/abl and has resistance to K562 cells[1], was used as an anticancer drug control to compare with curcumin. MTT was used to determine the proliferative effects of drugs on K562 and HL-60 cells. Western blot and flow cytometry were used to examine the abundance of signal protein molecules expressed in tumor cells. RESULTS: An exposure of K562 cells or HL-60 cells to Cur produced both concentration- and time-dependent increase in the anti-proliferative rate. Moreover, both cell lines had the same sensitivity to Cur (P>0.05). In contrast, HL-60 cells had more sensitivity to VP-16 than K562 cells in anti-proliferative effect (P